Games soldiers play. - Macedonia, M.
Computer games and virtual reality are radically altering the way the military prepares for war. Over the last three decades, sophisticated computer modeling and graphics, faster processor speeds, and advances in artificial intelligence have gone into building simulation technology that can create a reality that stops just short of war. In turn, the use of simulators has helped bring about a sea change in military training. Troops today practice exhaustively, taught by simulators not only how to use their ever more complex equipment, but also how to work in teams, move efficiently through a battlespace, and negotiate a wide range of conflicts, which may or may not involve military force. Simulation also gives military and political leaders insight into potential conflicts. Commanders can now recreate on computer the complex choreography of thousands of soldiers, weapons, vehicles, and aircraft moving across a battlefield that extends over thousands of square kilometers. In this way, military decision-makers can test strategic options before launching a campaign in earnest. They can also assess the performance of new weapons systems under consideration
Keywords: US military; Artificial intelligence; Battlespace; Computer games; Computer modeling; Military decision making; Strategic option testing; Virtual reality; War preparation; Weapons systems